Gut Microbiota and Metabolites in Atrial Fibrillation Patients and Their Changes after Catheter Ablation - Kang Huang; Yuegang Wang; Yang Bai; Qiuyan Luo; Xuancai Lin; Qiuyu Yang; Shihao Wang; Hongjie Xin (Microbiology Spectrum, 2022)
ABSTRACT The gut microbiota has been shown to be associated with multiple cardiovascular diseases, but there is little research on the gut microbiota and atrial fibrillation (AF); thus, how the gut microbiota and metabolites change in AF patients after catheter ablation is unclear. In this study, we used 16S rRNA high-throughput sequencing and nontargeted metabolomic detection to conduct horizontal and longitudinal analyses of the gut microbiota and metabolites of AF patients. Compared with a control group, species richness and diversity increased significantly in AF patients. Among them, opportunistic pathogenic bacteria, such as Klebsiella, Haemophilus, Streptococcus, and Enterococcus, were significantly increased, and symbiotic bacteria, such as Agathobacter and Butyrivibrio, were significantly reduced. After catheter ablation, intestinal symbiotic bacteria (Lactobacillus, Agathobacter, Lachnospira, etc.) were increased in most AF patients, while pathogenic bacteria (Ruminococcus, etc.) were reduced. Moreover, in AF patients, caffeine, which was negatively correlated with Klebsiella, was downregulated, and estradiol and ascorbic acid, which were positively correlated with Agathobacter, were also downregulated. After catheter ablation, citrulline, which was positively correlated with Ralstonia and Lactobacillus, was increased. Oleanolic acid, which was negatively correlated with Ralstonia was downregulated. In conclusion, our results not only show overall changes in the gut microbiota and metabolites in AF patients but also indicate their changes in the short term after catheter ablation. These data will provide novel possibilities for the future clinical diagnosis and treatment of AF. IMPORTANCE Gut microbiota and metabolites play a very important role in human health and can not only assess human health but also treat and prevent diseases. We analyzed the characteristics of the microbiota and metabolites in the human gut and found the effect of disease on gut microbiota and metabolites, which may be of important value in the pathogenesis of atrial fibrillation. At the same time, we also observed dynamic changes in gut microbiota and metabolites with the intervention of catheter ablation, which was not available in previous studies.